2006
DOI: 10.1038/nature04843
|View full text |Cite
|
Sign up to set email alerts
|

The calmodulin pathway and evolution of elongated beak morphology in Darwin's finches

Abstract: A classic textbook example of adaptive radiation under natural selection is the evolution of 14 closely related species of Darwin's finches (Fringillidae, Passeriformes), whose primary diversity lies in the size and shape of their beaks. Thus, ground finches have deep and wide beaks, cactus finches have long and pointed beaks (low depth and narrower width), and warbler finches have slender and pointed beaks, reflecting differences in their respective diets. Previous work has shown that even small differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
437
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(453 citation statements)
references
References 14 publications
15
437
0
1
Order By: Relevance
“…An elegant combination of a candidate gene approach and microarray analysis has recently revealed molecules associated with different outcomes of embryonic development of the beak in Darwin's finches. A single factor, the bone morphogenetic protein 4 precursor (BMP4), appears to promote a deeper and wider beak (Abzhanov et al, 2004) whereas higher local expression of Ca 2 þ calmodulin-dependent protein kinase phosphatase (CaM) is associated with elongation of the beak (Abzhanov et al, 2006). Variation in beak shape along these different axes neatly matches different species of Darwin's Finches' ability to feed on seeds of different sizes (Bowman, 1961).…”
Section: Speciation and Sex-linked Genesmentioning
confidence: 99%
“…An elegant combination of a candidate gene approach and microarray analysis has recently revealed molecules associated with different outcomes of embryonic development of the beak in Darwin's finches. A single factor, the bone morphogenetic protein 4 precursor (BMP4), appears to promote a deeper and wider beak (Abzhanov et al, 2004) whereas higher local expression of Ca 2 þ calmodulin-dependent protein kinase phosphatase (CaM) is associated with elongation of the beak (Abzhanov et al, 2006). Variation in beak shape along these different axes neatly matches different species of Darwin's Finches' ability to feed on seeds of different sizes (Bowman, 1961).…”
Section: Speciation and Sex-linked Genesmentioning
confidence: 99%
“…It was recently shown that different levels of expression of a single gene might have resulted in the markedly different beak shapes and lengths of Darwin's finches. Experimental overexpression of the calmodulin gene in chicken embryos resulted in a significant increase in the length of their beaks (120,121) . These experiments suggest that small and seemingly insignificant changes can have profound implications for the evolution of anatomical size and shape and thereby provide great potential for explaining the origins of phenotypic variation (122) , including increases in brain and skull size.…”
Section: Buiding a Big Brainmentioning
confidence: 99%
“…Studies on Darwin's finches have shown that the differences in the size and the shape of their beaks are related to the size of the regions where these neural crest cells recruit BMP4 (bone morphogenetic protein-4, which is responsible for the beak shape), BMP2 and BMP7 (for the size of the beak), as well as calmodulin (Abzhanov et al, 2006).…”
Section: Gene Recruitment By Neural Crest Cellsmentioning
confidence: 99%